Ginsenoside Rg2 alleviates myocardial fibrosis by regulating TGF-β1/Smad signalling pathway. (1st January 2021) - Wang, Quanwei; Fu, Wenwen; Yu, Xiaofeng; Xu, Huali; Sui, Dayun; Wang, Yeling
Abstract: Context: Panax ginseng C.A. Meyer (Araliaceae) has cardioprotective effects. Ginsenosides are responsible for most of the pharmacological activities of ginseng. Objective: This study investigates the effect of ginsenoside Rg2 on myocardial fibrosis in myocardial ischaemia rats. Materials and methods: Male Wistar rats were divided into control, isoproterenol, ginsenoside Rg2 (5, 20 mg/kg) groups ( n = 8). The rats were subcutaneously injected with isoproterenol (5 mg/kg) or normal saline (control group) once daily for 7 days. The animals were intragastrically treated with ginsenoside Rg2 or 0.5% CMC-Na (control and isoproterenol groups) daily for 28 days. At day 28, cardiac function, myocardial fibrosis, and TGF-β1/Smad signalling pathway were evaluated. Results: Compared with myocardial ischaemic rats, ginsenoside Rg2 at doses of 5, 20 mg/kg abated partially the augment of LVEDP (8.9 ± 1.3 vs. 7.5 ± 0.7, 7.2 ± 1.0 mmHg) and the decreases of the LVSP (96.75 ± 13.2 vs. 118.3 ± 19.4, 124.3 ± 21.3 mmHg), the + dp/dt (2142.8 ± 309.3 vs. 2598.6 ± 404.0, 2661.5 ± 445.2 mmHg/s), and the -dp/dt (1996.3 ± 306.3 vs. 2476.6 ± 289.7, 2509.6 ± 353.1 mmHg/s). Ginsenoside Rg2 (9.2 ± 0.9%, 8.5 ± 0.8%) alleviated myocardial fibrosis when compared with the isoproterenol group (10.1 ± 1.0%), which was accompanied by suppressed TGF-β1/Smad signalling in heart tissues. Conclusions: Ginsenosides from ginseng possess the property of alleviating myocardial fibrosis, improving cardiac function after myocardial ischaemia. Ginsenosides may be promising agents for improving the outcomes of patients with myocardial ischaemia.